Disproportionate impacts of building materials production facilities on neighboring communities - Alyson Kim; Gavin Chaboya; Helena Kwon; Sabbie A Miller (Environmental Research: Infrastructure and Sustainability)
The construction and building materials (CBMs) production industries, such as cement, steel, and plastics that are responsible for a substantial share of global CO _2 emissions, face increasing pressure to decarbonize. Recent legislative initiatives like the United States (US) federal Buy Clean Initiative and the World Green Building Council’s decarbonization plan for Europe highlight the urgency to reduce emissions during CBM production stages. However, there remains a gap in addressing the localized environmental and social impacts of these industries as well as a necessary understanding of how decarbonization efforts may change local impacts. This study introduces a framework for quantifying the disproportionate impacts ( I _d ) of 12 CBM production facility categories on communities of color and low-income demographics across the US. Using geographical and environmental data from the 2017 US National Emissions Inventory (NEI), we assess these impacts at four spatial scales: census tract, county, state, and national. Results show that across all scales, many CBM production facilities impose disproportionate impacts. The geographical disproportionate impact ( I _G,d ) shows the greatest burdens at the broadest spatial scales, whereas the environmental disproportionate impact ( I _E,d ) indicates highest burdens at more localized levels. Based on this spatial understanding, we provide methods that can be implemented to support community engagement and mitigate damages to populations neighboring industrial materials manufacturing. These findings offer valuable insights into the relationship between facility locations, emissions, and demographic groups, providing a basis for more targeted environmental justice policies aimed at mitigating these disproportionate impacts.